2017
DOI: 10.3389/fnhum.2017.00363
|View full text |Cite
|
Sign up to set email alerts
|

At the Leading Front of Neuroscience: A Bibliometric Study of the 100 Most-Cited Articles

Abstract: Background: It might be difficult for clinicians and scientists to identify comprehensively the major research topics given the large number of publications. A bibliometric report that identifies the most-cited articles within the body of the relevant literature may provide insight and guidance for readers toward scientific topics that are considered important for researchers and all relevant workers of academia. To our knowledge, there is a lack of an overall evaluation of the most-cited articles and hence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 25 publications
3
39
0
1
Order By: Relevance
“…Meanwhile, there are some inherent limitations in the use of ALE; for instance, some of the included studies had a relatively small sample size, which may lead to corresponding low statistical power and hence weaken the power of overall analysis (Lin et al., ). Also, ALE meta‐analysis focuses on consistency of activated brain locations but does not consider effect size of the activations (Eickhoff et al., ) and cannot model brain connectivity which is gaining popularity over the recent years (Yeung, Goto, & Leung, ,c,d; Yeung, Tanabe, Suen, & Goto, ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are some inherent limitations in the use of ALE; for instance, some of the included studies had a relatively small sample size, which may lead to corresponding low statistical power and hence weaken the power of overall analysis (Lin et al., ). Also, ALE meta‐analysis focuses on consistency of activated brain locations but does not consider effect size of the activations (Eickhoff et al., ) and cannot model brain connectivity which is gaining popularity over the recent years (Yeung, Goto, & Leung, ,c,d; Yeung, Tanabe, Suen, & Goto, ).…”
Section: Discussionmentioning
confidence: 99%
“…A replication award has been established by the Organization for Human Brain Mapping to recognize the best replication study in neuroimaging 1 . It was reported that publications of the neuroscience and particularly the neuroimaging fields have been growing steadily (Yeung et al, 2017a , b , c ), it could be intuitive to think that the number of published replication studies would also demonstrate a steady growth. However, Figure 3 has illustrated the annual publication count of replications fluctuated and never exceeded 20.…”
Section: Discussionmentioning
confidence: 99%
“…One useful metric to be evaluated would be the citation count of coronectomy papers. A bibliometric study identifies and evaluates the relevance of scientific publications with citation analysis, thus enabling a better understanding of the overall research landscape of a particular field . Instead of a qualitative evaluation of existing evidence or an investigation of the overall effect size, a bibliometric study on coronectomy literature can evaluate the influence of the body of the literature as a whole and identify the seminal works within it.…”
Section: Introductionmentioning
confidence: 99%